Pagan virtue in a Christian world : Sigismondo Malatesta and the Italian Renaissance - D'Elia, Anthony F. (Harvard University Press, 2016)
The Pope's wrath and the black legend 1 -- Court culture and the Renaissance in Rimini -- The Greek Renaissance and the return of the Paideia -- An ancient hero on Renaissance battlefields -- Astrology, Plato, and pagan worship -- Pagan sex and heroic virtue -- Questioning virtue in Malatesta literature -- Sigismondo's peril and defiance -- Conclusion: the pagan Renaissance.